Cognitive remediation for individuals with psychosis: efficacy and mechanisms of treatment effects. Issue 16 (8th September 2016) - Fiszdon, J. M.; Choi, K. H.; Bell, M. D.; Choi, J.; Silverstein, S. M.
Abstract : Background: The popularity of cognitive remediation (CR) interventions for individuals with psychosis is in part based on the well-established link between cognition and functioning and the assumption that by targeting cognition, function can improve. While numerous trials have reported CR's efficacy, it is still not considered an evidence-based treatment. Importantly, little is known about the mechanisms through which it may affect functioning. Method: In this study, we evaluated CR's proximal and distal effects, and examined potential mechanisms. A total of 75 individuals with psychotic disorders were randomized to a combination of strategy-based and drill-and-practice CR or wait-list control, with assessments of training task performance, neurocognition, functional capacity, symptoms and functioning conducted at baseline, end of the 2-month intervention, and 2-month follow-up. Results: Compared with treatment as usual, CR was associated with large post-training improvements on training tasks targeting attention, visuospatial memory, and verbal learning and memory, with persisting group differences at the 2-month follow-up. These generalized to mostly large improvements on neuropsychological measures targeting visuospatial memory, verbal learning and memory, delayed verbal memory and verbal working memory. While there were no CR-associated improvements on measures of functional capacity, symptoms, or a self-report measure of independent living skills, there was an effect on an interviewer-rated measure of functioning (Quality of Life Scale), which appeared primarily driven by the Intrapsychic Foundations subscale. Finally, for those randomized to CR, there were significant, medium-sized correlations between training task improvement, neuropsychological improvement and functioning measures. Conclusions: This suggests a complex, multifactorial relationship between CR, and cognitive and functional change.